Erotica in Mahabharata and Ramayana - D. Jupriono (International Journal of Educational Research & Social Sciences, 2021)
Pornography, which deliberately stimulates sexual desire as well as erotica, and as a story related to sexuality, is existed in shadow play, based on Ramayana and Mahabharata epics.   The text of shadow play, which has a source of both epics, is clean from pornography. If there are still parts of story in both epics which encourage the issue of sexual desire, all of them are identified erotica, not pornography. In this case, it is not mistaken if the moral education observers convince shadow play or wayang as source of national character value. However, shadow play in the stage performance is different, it is full with texts of pornography. At this point, it shows a dilemma: as national cultural heritage which is full with moral, character, and local wisdom values, wayang has to be held, conserved and developed by removing element of pornography; on the other hand, the stage performance of wayang can only survive with penetration of market taste by compromising addition of pornography elements.